Sphagnum-Dwelling Testate Amoebae in Bulgaria - Milcho Todorov (Pensoft Publishers, 2019)
The aim of this atlas is to present summarised information and to illustrate comprehensively the shell morphology and structure of the majority of recorded Sphagnum-dwelling testate amoebae in Bulgaria (a total of 120 species, each of them illustrated with 9 LM and SEM photos). Since most of these species appear to be widely distributed in Europe, as well as in many other regions of the world, the atlas may be of interest to all researchers on testate amoebae and can also be used by specialists in ecology, hydrobiology, palaeoecology and environmental monitoring.